2005
DOI: 10.1002/nav.20079
|View full text |Cite
|
Sign up to set email alerts
|

A decomposition algorithm applied to planning the interdiction of stochastic networks

Abstract: Abstract:We describe the application of a decomposition based solution method to a class of network interdiction problems. The problem of maximizing the probability of sufficient disruption of the flow of information or goods in a network whose characteristics are not certain is shown to be solved effectively by applying a scenario decomposition method developed by Riis and Schultz [Comput Optim Appl 24 (2003), 267-287]. Computational results demonstrate the effectiveness of the algorithm and design decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Examples have been reported in the literature for some time, and include server location [28], batch sizing [21], electricity generation unit commitment [37], supply chain design [34], network interdiction [6,15,17], and many others [38]. The general combinatorial, NP-hard nature of integer and mixed-integer problems makes them difficult to solve even when all the data are known, but special structure may allow for easier solution.…”
Section: Introductionmentioning
confidence: 99%
“…Examples have been reported in the literature for some time, and include server location [28], batch sizing [21], electricity generation unit commitment [37], supply chain design [34], network interdiction [6,15,17], and many others [38]. The general combinatorial, NP-hard nature of integer and mixed-integer problems makes them difficult to solve even when all the data are known, but special structure may allow for easier solution.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithmic treatment of stochastic two-stage problems with the excess probability objective leads to linear programs with (additional) binary variables, which indicate for each scenario whether the cost threshold η has been exceeded or not. This is for example discussed in [72,93], and has been applied in [53]. In principle, the ideas from the finite dimensional linear case could be transferred to the infinite dimensional setting of the shape optimization problem with excess probability.…”
Section: Risk Measuresmentioning
confidence: 99%
“…They formulate the problem of identifying locations for installing smuggled nuclear material detectors as a two-stage stochastic mixed-integer program with recourse, and showed that the problem is NP-Hard. In Held, Hemmecke, Woodruff [12], the stochastic network interdiction problem is shown to be solved effectively by applying a decomposition-based method. Our approach to solving the problem is akin to that proposed by Cormican in her master's thesis [3], where she proposes using Bender's decomposition to solve a deterministic version of the problem.…”
Section: Introductionmentioning
confidence: 99%